1999
DOI: 10.1210/jcem.84.5.5683
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Molecular Defects of the CYP21 Gene in Patients with Premature Adrenarche

Abstract: On the basis of hormonal studies, the incidence of defective steroidogenesis in children with premature adrenarche (PA) in the various reports ranges from 0-54%. Molecular studies have not been reported to date. The aim of the present study was to search for defects in the CYP21 gene in children with PA and to detect possible correlations of the molecular defect to pertinent hormonal and clinical data. In 48 children with PA (40 females and 8 males) and without signs of virilization, a Synachten test and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 19 publications
2
25
1
6
Order By: Relevance
“…Previous reports have shown higher (15) or similar frequencies (17,33,34) of heterozygosity in both PP children and hyperandrogenic women. However, some of these studies included patients with NCAH (15), were performed in unselected groups of hirsute women (34), or included different racial groups (17).…”
Section: Discussionmentioning
confidence: 67%
“…Previous reports have shown higher (15) or similar frequencies (17,33,34) of heterozygosity in both PP children and hyperandrogenic women. However, some of these studies included patients with NCAH (15), were performed in unselected groups of hirsute women (34), or included different racial groups (17).…”
Section: Discussionmentioning
confidence: 67%
“…Most girls are asymptomatic at birth and may present later on with premature pubarche during childhood, hirsutism and/or menstrual irregularities during adolescence, subfertility in later life or a phenotype resembling polycystic ovary syndrome. 71,73,74 Several mutations in the CYP21A2 gene have been described with a broad overlap with regard to the degree of virilization and a variable genotype-phenotype correlation.The concordance between phenotype and genotype varies in the different forms, being 100% in the salt-losing variety. 70,75 11β-hydroxylase deficiency (CYP11Β1) represents about 5-8% of CAH cases and occurs in 1 out of 200,000 live births.…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%
“…In our previous two papers in Greek hyperandrogenic women, it was estimated that the frequency of NC-CAH was about 5%; however, a great number of women that reached the 11% had hormonal levels compatible with a possible heterozygosity of 21-OHdef [38,39]. Dacou Voutetakis et al in a substantial sample of children from Greece with premature adrenarche reported a high incidence of molecular defects of CYP 21 gene that reached to 33% [40]. The genetic linkage disequilibrium between 21-OHdef and HLA phenotypes B 14, DR 1 , B 35 , B 7 and B 44 has been reported in many studies in the Caucasian populations and the Jewish Ashkenazi as well as in the populations around the Mediterranean.…”
Section: Discussionmentioning
confidence: 95%